2006
DOI: 10.2109/jcersj.114.445
|View full text |Cite
|
Sign up to set email alerts
|

SiC-Based Ceramic Fibers Prepared via Organic-to-Inorganic Conversion Process-A Review

Abstract: Review péÉÅá~ä fëëìÉ Äó dìÉëí bÇáíçêëW lêÖ~åáÅ-íç-fåçêÖ~åáÅ`çåîÉêëáçå mêçÅÉëë Ñçê mçäóãÉê-aÉêáîÉÇ`Éê~ãáÅë pá`_~ëÉÇ`Éê~ãáÅ cáÄÉêë mêÉé~êÉÇ îá~lêÖ~åáÅíçfåçêÖ~åáÅ çåîÉêëáçå mêçÅÉëë-^oÉîáÉï ሱᑿ-ᠪᑿং၁ɟɵɃɁǺȗȚ SiC ṾɃɱɧɋȷέỺǽ۰༔ ἕ◻Several types of Si-based ceramic fibers have been prepared using an organic-to-inorganic conversion process. In this article, the preparation, microstructure, and high-temperature stability of SiC-based ceramic fibers prepared from polycarbosilane of an organosilicon polymer are reviewed. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 70 publications
(41 reference statements)
0
46
0
1
Order By: Relevance
“…Therefore, they can be subjected to a large variety of different forming methods, some of them unique or at least much more easily exploitable for polymers than ceramic powders or pastes. These include casting (Melcher et al 2003), infiltration (Satoa et al 1999), pressing (Galusek et al 2007), injection moulding (Walter et al 1996), extrusion (Eom & Kim 2007;Eom et al 2008), machining (Rocha et al 2005), fibre drawing (Okamura et al 2006), blowing/ foaming (Colombo 2008), ink jetting (Mott & Evans 2001), rapid prototyping (Friedel et al 2005), electrohydrodynamic spraying/spinning ), aerosol spraying (Bahloul-Hourlier et al 2001, self-assembly (Malenfant et al 2007) and microcomponent processing such as UV/X-ray lithography, nano/micro-casting, replication, micro-extrusion and embossing/forging (Schulz 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they can be subjected to a large variety of different forming methods, some of them unique or at least much more easily exploitable for polymers than ceramic powders or pastes. These include casting (Melcher et al 2003), infiltration (Satoa et al 1999), pressing (Galusek et al 2007), injection moulding (Walter et al 1996), extrusion (Eom & Kim 2007;Eom et al 2008), machining (Rocha et al 2005), fibre drawing (Okamura et al 2006), blowing/ foaming (Colombo 2008), ink jetting (Mott & Evans 2001), rapid prototyping (Friedel et al 2005), electrohydrodynamic spraying/spinning ), aerosol spraying (Bahloul-Hourlier et al 2001, self-assembly (Malenfant et al 2007) and microcomponent processing such as UV/X-ray lithography, nano/micro-casting, replication, micro-extrusion and embossing/forging (Schulz 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The KD-S SiC fibres used in this study were produced by our laboratory using the procedure of Yajima [2,5]. These nearstoichiometric SiC fibres were obtained by adding hydrogen to eliminate excess carbon during sintering process.…”
Section: Methodsmentioning
confidence: 99%
“…Silicon carbide materials could be oxidized in the passive/active oxidation regime, which is influenced by the purity and microstructure of materials, as well as the temperature and oxygen partial pressure [2]. Previous studies have confirmed that SiC fibres with low oxygen content would be passively oxidized in both wet air and dry air [12].…”
Section: Effects Of Steam On the Oxidation Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…For making a bulk body, suppressing critical crack formation during pyrolysis is a prerequisite even if minor ones could be admissible. By taking into account the fact that a polymeric preform of high specific surface such as fibers 18), 19) and particles 20), 21) can be well consolidated into an almost crackfree pyrolyzed product, it is expected that high specific surface and simple and continuous geometry contribute to reducing crack initiation. Those could work well for sound consolidation through shortening gas elimination pathway and unifying thermal shrinkage distribution.…”
Section: )13)mentioning
confidence: 99%